Graduates of 2-Year Engineering and Engineering Technician Programmes in the U.S. and the U.K. - Reys-Nickel, Lynsey; Lasonen, & Johanna (Journal of Technical Education and Training, 2018)
In the U.S. and the U.K., the demand for a skilled and educated workforce of engineers and engineering technicians is greater than the supply. Postsecondary institutions in the U.S. awarding associate’s degrees in engineering and engineering technologies will fail to keep pace with job growth projections if trends of low and slow graduation rates continue. The purpose of this study was to identify the characteristics of attendees and graduates of associate’s degree programmes in engineering and engineering technologies and determine whether and to what extent graduation is a function of student-related and institutional variables. Researchers used an ex post facto design using the 2004/2009 Beginning Postsecondary Students Longitudinal Study (BPS:04/09) dataset from the U.S. Department of Education’s National Center for Education Statistics (NCES). Descriptive statistics indicated graduates were mostly White, married, middle income, employed part-time, enrolled full-time, completed Trigonometry/Algebra II, had a father who’s highest education level was an associate’s degree, did not know their mother’s highest level of education, completed remedial coursework, and started college with the goal of an associate’s degree. Logistic regression results indicated that gender and enrollment size during the 2003-2004 academic year significantly predicted associate’s degree completion in engineering and engineering technologies. This study provided a current description of students pursuing sub-baccalaureate engineering and engineering technologies programmes in the U.S.. However, given the small weighted sample size, the regression was inconclusive in terms of the model’s predictive ability. Therefore, future caution should be taken when analysing national, educational datasets to address national workforce shortages.